PELATIHAN PENGGUNAAN MEDIA PEMBELAJARAN ICT UNTUK MENINGKATKAN KEMAMPUAN GURU DI SDN CIBENING 01 - Ilham Z.A, Moch; Suryani, Elvira; Irham (Universitas Islam 45 Bekasi, 2025)
Based on observations conducted in the area, particularly at the elementary school level, teachers in Cibening Village still make very limited use of learning resources, especially those based on information and communication technology (ICT). This condition is largely due to the lack of training provided to teachers in the use of technology and ICT-based teaching aids, which results in limited knowledge and skills in utilizing digital learning media. Consequently, the learning process tends to rely on conventional methods that are less interactive and innovative. Therefore, a workshop on the use of ICT-based learning media was organized as part of this community service program in order to enhance teachers’ ability to integrate technology into the learning process. The program was implemented through training activities held at SDN Cibening 01, Cibening Village, with the target participants being the teachers at SDN Cibening 01. The impact of this training program is an increase in teachers’ motivation to utilize ICT-based learning media, thereby making the learning process more engaging, interactive, and effective in improving students’ comprehension. In addition, this program is expected to provide teachers with new insights in creating more creative and technology-based learning innovations, ultimately contributing to the improvement of education quality in elementary schools in Cibening Village.